State and Regional Payments Mechanisms: Comment - Pfister, Richard L. (Quarterly Journal of Economics, 1960)
Journal Article State and Regional Payments Mechanisms: Comment Get access Richard L. Pfister Richard L. Pfister Dartmouth College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 74, Issue 4, November 1960, Pages 641–648, https://doi.org/10.2307/1884359 Published: 01 November 1960